Symbolism and meaning in Hausa Proverbs: A Window into Cultural Values and Worldview - Abdulwaheed, Shuaibu; Aliyu, Uba (Journal of Natural Language and Linguistics, 2025)
This research investigates how Hausa proverbs function as native wisdom expressions which teach societal practices together with moral teachings to the Hausa ethnolinguistic population who inhabit northern Nigeria and the Sahel region. The research bases its analysis on Semiotics Theory and Ethnolinguistic Vitality Theory to study selected proverbs and their metaphorical composition and messaging. The study defines three primary concepts which embrace moral leadership together with societal unity and explain spiritual forces and human free will. Two proverbs which illuminate core communal principles of interpersonal conduct are Ramin mugunta a gina shi gajere (Dig a pit of evil shallow) and Zumunta a ƙafa take (Good relationships depend on feet). Hausa proverbs survive actively in democratic discourses together with educational and media content even though modernization trends and digital communication techniques challenge their establishment. Through the use of animals and natural references alongside common experiences proverbs teach the preservation of traditional wisdom and maintain awareness of time-tested knowledge. The research validates Hausa proverbs as strong linguistic and cultural tools which showcase Hausa identity in its traditional roots as well as contemporary surroundings.